2017
DOI: 10.1007/s10157-017-1447-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for progression of chronic kidney disease in the EPPIC trials and the effect of AST-120

Abstract: BackgroundTwo randomized, double-blind, placebo-controlled trials (EPPIC-1 and EPPIC-2) investigated the efficacy and safety of AST-120, an oral spherical carbon adsorbent, in adults with chronic kidney disease (CKD). While the benefit of adding AST-120 to standard therapy was not supported by these trials, we performed a post hoc analysis to focus on CKD progression and to determine the risk factors for the primary endpoint in the EPPIC trial population.MethodsIn the EPPIC trials, patients were randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Other studies have shown an association of microhaematuria with faster CKD progression [17]. Findings from the Chronic Renal Insufficiency Cohort (CRIC) study and the Evaluating Prevention of Progression in Chronic Kidney Disease (EPICC) trial, suggest an increased risk or ESRD after two years of follow-up in patients with baseline haematuria [18]. We now present the first study analysing the association of haematuria with disease severity and outcomes in a large population of biopsy-proven ATIN patients.…”
Section: Discussionmentioning
confidence: 89%
“…Other studies have shown an association of microhaematuria with faster CKD progression [17]. Findings from the Chronic Renal Insufficiency Cohort (CRIC) study and the Evaluating Prevention of Progression in Chronic Kidney Disease (EPICC) trial, suggest an increased risk or ESRD after two years of follow-up in patients with baseline haematuria [18]. We now present the first study analysing the association of haematuria with disease severity and outcomes in a large population of biopsy-proven ATIN patients.…”
Section: Discussionmentioning
confidence: 89%
“…In experimental CKD, it reduces tissue accumulation of IS and pCS in diverse tissues, including the kidney and protected the kidneys in several animal models of AKI and CKD [ 122 ], However, two large multinational trials (EPPIC-1 and EPPIC-2), failed to show benefit on CKD progression [ 123 ]. However, a post-hoc, hypothesis-generating analysis observed that in the subgroup of high risk patients (urinary creatinine ratio ≥1.0 and haematuria) who were additionally treated with renin-angiotensin system blockade, AST-120 may have provided additional benefit in retarding CKD progression [ 124 ]. The large daily number of pills may negatively impact compliance and may be one of the underlying cause for the failure of clinical trials outside Japan.…”
Section: Nephroprotection Interventional Studies Targeting the Intmentioning
confidence: 99%
“…A subanalysis in the patients enrolled in the study in the USA showed a delay in the treated group for reaching the primary endpoint which was a composite of RRT and doubling of serum creatinine [ 491 ], and this evolution was essentially observed in the group with diabetic nephropathy [ 491 ]. A further post hoc analysis showed that the benefit of AST-120 was limited to patients on ACEi/ARB with hematuria and urinary protein/creatinine ratio ≥ 1 [ 492 ], although this type of post hoc subgroup analysis is prone to substantial bias, especially as hematuria, as one of the parameters accounted for, is far from specific for intrinsic kidney disease.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%